The Middle Carboniferous Boundary in the North of Pay-Khoy – Correlation between the Shallow- and Deep-Water Sequences - A.V. Zhuravlev; Ya.A. Vevel (Учёные записки Казанского университета: Серия Естественные науки)
The paper considers the Lower-Middle Carboniferous boundary interval in the sections of the Pay-Khoy carbonate parautochthone (shallow-water facies) and the Kara slate allochthone (deep-water facies) with respect to the boundary tracing criteria. The boundary interval has been studied in the sections of the North-Eastern Pay-Khoy (Peschanaya River, Khardto Lake, Barents Sea shore near the Chaika Cape, and Lymbad”yakha River). The boundary recognition has been based on data for the conodonts and foraminifers. The boundary is not directly characterized by fauna in either deep- or shallow-water facies. The boundary interval has been recognized by the latest findings of the Early Carboniferous foraminifers and conodonts (Parastaffella cf. angulata, Gnathodus bollandensis), as well as the first findings of Declinognathodus noduliferus in the upper part of the Bolvanskiy Formation of the carbonate parautochthone. The transgression maximum has been detected in the boundary interval. In the sections of the slate allochthone, the boundary may coincide with the base of the Karasilova Formation. The lower part of the formation is characterized by condensed sequence (transgression maximum), and the first findings of the Middle Carboniferous conodonts (Rhachistognathus minutus) correspond to the upper part of the Syuransk Substage. The transgression maximum is considered as the reliable boundary marker. The traces of the transgression maximum have been detected in the upper part of the Bolvanskiy Formation and in the base of the Karasilova Formation.